The Rhetorical Organization of Oral Presentations in the Medical Specialty of Pneumology - Carvalho, Keila Rocha Reis de (The ESPecialist, 2011)
This study aims at analysing the rhetorical organization of 30 oral presentations in English in the medical specialty of pneumology. The theoretical background lays on Genre Analysis (Swales, 1990) and research articles in the medical area described by Nwogu (1997). Results show that the rhetorical organization of the oral presentations is similar to that of research articles in the medical area, with differences specially in the Introduction section and at the end of the Discussion section. The differences found emphasize the oral aspects of the oral presentations, suggesting that they are samples of a genre with characteristics of the spoken language as well as of the written language.